SYNERGISTIC POTENTIAL OF NIGELLA SATIVA L. AND TRIGONELLA FOENUM-GRAECUM: INTEGRATED NETWORK PHARMACOLOGY FOR DIABETIC WOUND HEALING - DUHITA, MAHARANI RETNA; SUSILOWATI, RETNO; AINI, SITI QURROTUL; ANNISA, RAHMI (International Journal of Applied Pharmaceutics, 2024)
Objective: Diabetes Mellitus (DM) is a metabolic disorder marked by elevated blood glucose levels, and one of the issues linked to DM involves the development of Diabetic Wounds (DW). DW is susceptible to infection and develops into chronic wounds if not treated properly. This study aimed to investigate the network pharmacology of N. sativa L. and T. foenum-graecum, emphasizing on their potential as DW treatment candidates. Methods: Various databases were used in this study, including PubChem, Dr. Duke's phytochemistry and Ethnobotany, and KNApSAcK Family. Swiss Target Prediction and Way2Drug PASS Online were utilized for biological activity and protein target prediction. The DW pathway's protein-protein interactions were examined with the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, Gene Cards, and STRING databases. STRING was used to predict the metabolite's action. The relationship between metabolites and target proteins was predicted using STITCH, and Cytoscape was used to visualize the network. Result: The results showed that ten active ingredients (five active ingredients in N. sativa L. and five active ingredients in T. foenoem-graecum) contributed to DW healing by affecting Tumor Necrosis Factor (TNF), Interleukin-1beta (IL1B), JUN, Caspase 3 (CASP3), Interleukin-6 (IL-6), Alpha Kinase Threonine-1 (AKT1), Vascular Endothelial Growth Factor-A (VEGFA), and Mitogen-Activated Protein Kinase 3 (MAPK3) genes. Furthermore, the ten active ingredients correlated with twenty-eight intracellular proteins, resulting in a mechanism involving eight DW signalling pathways. Conclusion: Based on network pharmacology analysis, we determine that N. sativa L. and T. foenoem-graecum combination can potentially treat DW.